2018
DOI: 10.1590/0101-41614815137fedd
|View full text |Cite
|
Sign up to set email alerts
|

Diferenciais de Rendimentos entre Raças e Gêneros, nas Regiões Metropolitanas, por Níveis Ocupacionais: uma análise através do pareamento de Ñopo

Abstract: ResumoEste artigo busca analisar o comportamento dos diferenciais de rendimentos entre gênero e raças nas regiões metropolitanas (RMs) e o Distrito Federal, considerando diferentes categorias ocupacionais. Dada a disparidade regional, optou-se por corrigir a renda através do índice de custo de vida desenvolvido por Azzoni e Almeida (2016); para captar o diferencial, os efeitos dotação e discriminação, utilizou-se o método não paramétrico de Ñopo (2008), aplicado aos dados obtidos pela PNAD (2014). Além disso, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 10 publications
0
4
0
17
Order By: Relevance
“…The returns of the gender variable female and the nonwhite race variable, in general, corroborate the literature on income differential, pointing out negative coefficients, except for some values in the lower and upper quantiles of the income distribution that were positive, specifically in the rural–urban workers. Among other authors who show “discrimination” of income by sex and race are: Moraes (2005), Mattos and Machado (2006), Bartalotti and Leme (2007), Machado et al (2008), Mariano et al (2016) and Pereira and Oliveira (2016). As for the return of activities, it is observed, for the year 2005, in the three groups of workers, there was no well-defined trend in the quantiles.…”
Section: Resultsmentioning
confidence: 92%
“…The returns of the gender variable female and the nonwhite race variable, in general, corroborate the literature on income differential, pointing out negative coefficients, except for some values in the lower and upper quantiles of the income distribution that were positive, specifically in the rural–urban workers. Among other authors who show “discrimination” of income by sex and race are: Moraes (2005), Mattos and Machado (2006), Bartalotti and Leme (2007), Machado et al (2008), Mariano et al (2016) and Pereira and Oliveira (2016). As for the return of activities, it is observed, for the year 2005, in the three groups of workers, there was no well-defined trend in the quantiles.…”
Section: Resultsmentioning
confidence: 92%
“…A steady stream of research since Silva (1978Silva ( , 1980Silva ( , 1985 and Oliveira, Porcaro, and Araújo (1981) has shown that the unexplained wage gaps between whites and nonwhites in Brazil are similar to those in the U.S., despite differences in the historical background and legal setting. 5 Several studies have shown that the gaps are especially large at the top of the distribution, pointing to the scarcity of nonwhites in high-paying industries and occupations (Soares, 2000;Henriques, 2001;Campante, Crespo, and Leite, 2004;Chadarevian, 2011;Mariano et al, 2018). Similar patterns have been documented in other Latin American countries (e.g., Nopo, 2012).…”
mentioning
confidence: 74%
“…Under another scientific methodology for the study of wage inequalities, Mariano et al (2018) used the Ñopo pairing with 2014 PNAD data for metropolitan regions of Brazil and found a wage gap in favor of men and whites.…”
Section: Salary Inequalities Theories and Methods: A Literature Reviewmentioning
confidence: 99%